Implementation of an Innovative Nurse-Delivered Depression Intervention for Mothers of NICU Infants. (April 2015) - Chuffo Siewert, Rebecca; Cline, Michelle; Segre, Lisa S.
Abstract : Depression affects approximately 19% of all postpartum women, and mounting evidence indicates increased risk for mothers of preterm infants, with prevalence estimates ranging from 28% to 67%. The current approach to management of maternal symptoms related to postpartum depression in the neonatal intensive care unit (NICU) ranges from no intervention to depression screening and referral. For depressed mothers of NICU infants, obtaining treatment is especially difficult and usually becomes a secondary priority; thus, we looked to a nurse-delivered counseling model. Listening visits (LV) are an empirically supported nurse-delivered intervention that focuses on relationship building and exploration of a mother's problems through active reflective listening and collaborative problem solving. An LV open trial in the NICU has been conducted to evaluate the effectiveness of this intervention for mothers of hospitalized infants. Results indicate that LV are associated with a reduction in both maternal depressive and anxiety symptoms. This case study following the description of the intervention demonstrates how the authors used the experiences from the NICU open trial to expand the application of LV to this new setting.